Sex-Related Overactivation of NLRP3 Inflammasome Increases Lethality of the Male COVID-19 Patients - Zhang, Hongliang; Tang, Yujie; Tao, Jinhui (Frontiers in Molecular Biosciences, 2021)
The COVID-19 pandemic, caused by SARS-CoV-2 infection, remains a dramatic threat to human life and economic well-being worldwide. Significant heterogeneity in the severity of disease was observed for patients infected with SARS-CoV-2 ranging from asymptomatic to severe cases. Moreover, male patients had a higher probability of suffering from high mortality and severe symptoms linked to cytokine storm and excessive inflammation. The NLRP3 inflammasome is presumably critical to this process. Sex differences may directly affect the activation of NLRP3 inflammasome, impacting the severity of observed COVID-19 symptoms. To elucidate the potential mechanisms underlying sex based differences in NLRP3 activation during SARS-CoV-2 infection, this review summarizes the reported mechanisms and identifies potential therapeutic targets.